박판주조법으로 제조한 Al-8Zn-2.5Mg-xCu 합금 판재의 미세조직에 미치는 Cu의 영향 - 김동국; Dong-guk Kim; 조용희; Yong Hee Jo; 이윤수; Yun-soo Lee; 김용유; Yong-you Kim; 김형욱; Hyoung-wook Kim; 김정기; Jung-ki Kim (대한금속·재료학회지, 60(4), 2022)
The effect of Cu content on the microstructure and mechanical properties of Al-8.0Zn-2.5Mg-xCu (x: 0, 1, 2, 3) aluminum alloys manufactured by the twin-roll casting process was investigated. The Al-8.0Zn-2.5Mg-xCu alloy showed an increase in surface defects with increasing Cu content. This is because the amount of residual liquid in the final solidification region increased from 9.6 wt.% to 18.3 wt.% as the Cu content increased from 0Cu to 3 Cu alloy. For the 3Cu alloy, as the amount of residual liquid in the final solidification region exceeded the critical point, a large number of surface defects and internal shrinkage defect were observed. The main secondary phases of the four alloys were the T(Mg 32 (Al, Zn) 49 ) and η(MgZn 2 ) phases, and their fraction increased with Cu content. These secondary phases mainly existed in the center segregation band, and a fine η(MgZn 2 ) phase was additionally observed. In terms of mechanical properties, as the Cu content increased, the hardness of the center matrix, secondary phase, and overall hardness increased respectively. Although the yield strength increased, the tensile strength and elongation decreased because the center segregation band was widened from 684 μm to 790 μm with increasing Cu content. (Received 18 October, 2021; Accepted 4 January, 2022)